Biological therapy in systemic lupus erythematosus, antiphospholipid syndrome, and Sjögren’s syndrome: evidence- and practice-based guidance - Marinho, António; Delgado Alves, José; Fortuna, Jorge; Faria, Raquel; Almeida, Isabel; Alves, Glória; Araújo Correia, João; Campar, Ana; Brandão, Mariana; Crespo, Jorge; Marado, Daniela; Matos-Costa, João; et al. (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE), antiphospholipid syndrome (APS), and Sjogren’s syndrome (SS) are heterogeneous autoimmune diseases. Severe manifestations and refractory/intolerance to conventional immunosuppressants demand other options, namely biological drugs, and small molecules. We aimed to define evidence and practice-based guidance for the off-label use of biologics in SLE, APS, and SS. Recommendations were made by an independent expert panel, following a comprehensive literature review and two consensus rounds. The panel included 17 internal medicine experts with recognized practice in autoimmune disease management. The literature review was systematic from 2014 until 2019 and later updated by cross-reference checking and experts’ input until 2021. Preliminary recommendations were drafted by working groups for each disease. A revision meeting with all experts anticipated the consensus meeting held in June 2021. All experts voted (agree, disagree, neither agree nor disagree) during two rounds, and recommendations with at least 75% agreement were approved. A total of 32 final recommendations (20 for SLE treatment, 5 for APS, and 7 for SS) were approved by the experts. These recommendations consider organ involvement, manifestations, severity, and response to previous treatments. In these 3 autoimmune diseases, most recommendations refer to rituximab, which aligns with the higher number of studies and clinical experience with this biological agent. Belimumab sequential treatment after rituximab may also be used in severe cases of SLE and SS. Second-line therapy with baricitinib, bortezomib, eculizumab, secukinumab, or tocilizumab can be considered in SLE-specific manifestations. These evidence and practice-based recommendations may support treatment decision and, ultimately, improve the outcome of patients living with SLE, APS, or SS.